2014
DOI: 10.5812/ircmj.9069
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Peripartum Care

Abstract: Background:Maternal health improvement is one of the eight goals of the third millennium development, set in 2000. Pregnancy complications are the most important causes of maternal mortality worldwide. Proper and qualified health care access is one the most important factors for reducing maternal and neonatal mortality rates.Objectives:This study aimed to determine quality of peripartum care in Lorestan province in 2013.Materials and Methods:This was a descriptive cross-sectional study, in which quality of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
3
8
1
Order By: Relevance
“…Concerning quality of CS nursing care the present study exposed that half of studied mothers had received incomplete care preoperative and perioperative. The current study finding in linewith the study of Changaee, et al (2014) in Iran about the quality assessment of perioperative CS care. Regarding the nursing care of postoperative, the current study indicated that, majorityof studied sample had received incomplete and below standard care which in the same line with (Lotto, 2015), who concluded that the quality of postnatal care presentedto clients was poor , below standard and nurses did not compliance withpredetermined guide-lines for managing postpartum mothers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning quality of CS nursing care the present study exposed that half of studied mothers had received incomplete care preoperative and perioperative. The current study finding in linewith the study of Changaee, et al (2014) in Iran about the quality assessment of perioperative CS care. Regarding the nursing care of postoperative, the current study indicated that, majorityof studied sample had received incomplete and below standard care which in the same line with (Lotto, 2015), who concluded that the quality of postnatal care presentedto clients was poor , below standard and nurses did not compliance withpredetermined guide-lines for managing postpartum mothers.…”
Section: Discussionsupporting
confidence: 91%
“…Table (5) reveals a highly statistically significance concerning women's satisfaction level and number of parity and history of caesarean section (P =0.005*), Also, number of gravida, number of abortion and gestational age with women's satisfaction level (p>0.05). Table ( 6) shows that, there was a highly statistically significance between all items of women's satisfaction and quality C S nursing care offered. Table (7) shows a positive association between quality of CS care with the level of women's satisfaction.…”
Section: Resultsmentioning
confidence: 88%
“…Each definition is reported in detail in Table 2. Some studies did not report whether soap use or handrub was necessary to achieve adequate hand hygiene and did not refer to guidelines that specifically do [20,22,24,26,27,29]; in addition often studies did not report if other aspects of hand hygiene such as the sequence of actions preceding or following hand washing/ rubbing, technique or duration were assessed in the summative compliance estimatesexcept for Gon Another aspect of the definition is the type of hand hygiene opportunity (when hand hygiene should occur). The WHO hand hygiene guidelines refer to five key hand hygiene opportunities: before clean/clean procedures, after exposure to body fluids, before touching the patient, after touching the patient, after touching the patient's surrounding.…”
Section: Definition Of Outcomementioning
confidence: 99%
“…Mannava et al reported a compliance 81% before gloving for delivery [27]. Simbar et al [29] and Changaee et al [20] reported on compliance during second stage of labour, although it was unclear whether compliance was before or after interaction with the patient or which type of interaction i.e. aseptic procedure, touching the patient.…”
Section: Definition Of Outcomementioning
confidence: 99%
“…1 The American College of Obstetricians and Gynecologists reported in 1998 that *500,000 women die annually across the world from causes related to pregnancy and childbirth. Onequarter of the cases are caused by complications in the third stage of labor, 2 an interval between delivery of the neonate and expulsion of the placenta.…”
Section: Introductionmentioning
confidence: 99%